Pemanfaatan Integrasi Smartwatch dan Aplikasi Forza dalam Meningkatkan Kinerja Tim Sepak Bola Putra Mangun Jaya F.C. - Tri Lathif Mardi Suryanto; Erna Daniati; Nur Cahyo Wibowo; Joko Mijiarto; Praja Firdaus Nuryananda; Aliyah Shafa Nurharyana (I-Com: Indonesian Community Journal, 2024)
Player management issues at the Putra Mangun Jaya (PMJ) football club prompted a team from Universitas Pembangunan Nasional Veteran Jawa Timur to conduct a socialisation of the use of smartwatches synchronised with the Forza App. This Community Service (PKM) aims to improve the management and players' understanding of the benefits of this technology in training and performance. Through socialisation and training, the management team's understanding of the use of smartwatches increased from 40% to 85%, this is because they now understand other functions of smartwatches, apart from being a time marker smartwatch can be used to monitor the performance of football players through synchronisation with the Forza App. This socialisation had a positive impact on management and players, showing that technology integration provides real benefits for football clubs and productive society, especially in the football activist community.